Augmentation of human neutrophil and alveolar macrophage LTB(4) production by N-acetylcysteine: role of hydrogen peroxide - Dent, Gordon (1997)
1. The actions of N-acetylcysteine (NAC) on hydrogen peroxide (H(2)O(2)) and leukotriene B(4) (LTB(4)) production by human resting and stimulated peripheral blood neutrophils and alveolar macrophages were investigated. 2. At a concentration of 100 μM, NAC significantly (P<0.01) suppressed the accumulation of H(2)O(2) in the incubation medium of resting and opsonized zymosan (OZ; 0.5 mg ml(−1))- or N-formylmethionyl-leucyl-phenylalanine (fMLP; 1 μM)-stimulated neutrophils and of resting and OZ-stimulated macrophages. At concentrations of 10 μM and above, NAC augmented significantly the level of LTB(4) in the supernatants of OZ- and fMLP-stimulated neutrophils (P<0.01 and P<0.05, respectively) and OZ-stimulated macrophages (P<0.05 at 10 μM, P<0.01 at 100 μM NAC). 3. NAC (100 μM) caused a significant (P<0.01) reduction in the quantity of measurable H(2)O(2) when incubated with exogenous H(2)O(2) concentrations equivalent to those released from OZ-stimulated neutrophils and macrophages. At no concentration did NAC affect quantitites of measurable LTB(4) when incubated with exogenous LTB(4). 4. Superoxide dismutase (SOD), which catalyzes the conversion of superoxide anion to H(2)O(2) had no significant effect on LTB(4) production by human neutrophils. In contrast, catalase, which catalyzes the conversion of H(2)O(2) to H(2)O and O(2), caused a pronounced, statistically significant (P<0.01) increase in the levels of LTB(4) measured in the supernatants of OZ- and fMLP-stimulated neutrophils. 5. H(2)O(2) (12.5 μM and 25 μM, concentrations equivalent to those measured in the supernatants of activated neutrophils and alveolar macrophages, respectively) caused a small (13%) decrease in the quantity of measurable LTB(4) (P=0.051 and P<0.05 at 12.5 μM and 25 μM, respectively) that was inhibited by NAC (100 μM) but not by catalase (400 u ml(−1)). 6. In conclusion, the anti-oxidant drug, NAC, increases LTB(4) production by human neutrophils and alveolar macrophages, probably through the elimination of cell-derived H(2)O(2). LTB(4) undergoes a H(2)O(2)-dependent oxidation that is inhibited by NAC but this is unlikely to account fully for the increased levels of LTB(4), suggesting that NAC may increase LTB(4) production by blocking the H(2)O(2)-dependent inhibition of a synthetic enzyme, such as 5-lipoxygenase.